2006
DOI: 10.7326/0003-4819-145-3-200608010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Victims of Cardiac Arrest Occurring Outside the Hospital: A Source of Transplantable Kidneys

Abstract: Outcomes of transplants from non-heart-beating donors and younger heart-beating donors are similar, and results for transplants from non-heart-beating donors improved compared with those from older heart-beating donors. On the basis of these results, the authors encourage other transplant units to adopt the use of type I and type II non-heart-beating donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(114 citation statements)
references
References 20 publications
5
102
0
7
Order By: Relevance
“…21 Liberal use of DCD kidneys may lead to considerable expansion of the donor pool but is associated with a relatively high incidence of delayed graft function and primary nonfunction. [12][13][14][15][16][17][18]22,23 In this study, graft failure in the first 3 months after transplantation was twice as likely for DCD kidneys than for CLINICAL EPIDEMIOLOGY www.jasn.org DBD kidneys; however, DCD kidneys that overcome the early posttransplantation period function as long as DBD kidneys [12][13][14][15][16][17][18] ; therefore, it is unclear whether dialysis patients who are on the waiting list should accept an offer for DCD kidney transplantation or continue dialysis treatment until a conventional DBD kidney is available.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…21 Liberal use of DCD kidneys may lead to considerable expansion of the donor pool but is associated with a relatively high incidence of delayed graft function and primary nonfunction. [12][13][14][15][16][17][18]22,23 In this study, graft failure in the first 3 months after transplantation was twice as likely for DCD kidneys than for CLINICAL EPIDEMIOLOGY www.jasn.org DBD kidneys; however, DCD kidneys that overcome the early posttransplantation period function as long as DBD kidneys [12][13][14][15][16][17][18] ; therefore, it is unclear whether dialysis patients who are on the waiting list should accept an offer for DCD kidney transplantation or continue dialysis treatment until a conventional DBD kidney is available.…”
Section: Discussionmentioning
confidence: 79%
“…As a consequence, the incidence of delayed graft function and primary nonfunction in DCD kidney transplantation is relatively high, although survival of functioning grafts seems to be satisfactory. [12][13][14][15][16][17][18] During the past decade, DCD has evolved into routine clinical practice that currently supplies Ͼ10% of all deceased-donor kidneys in the United States and up to 50% in the Netherlands; however, it is unknown whether patients who receive a DCD kidney live longer than patients who receive conventional therapy (i.e., continue dialysis treatment with the option of later receiving a DBD kidney). We therefore evaluated the effect of kidney transplantation from different types of deceased donors on the survival of dialysis patients who were on the waiting list in an observational cohort study including all patients who were registered on the Dutch waiting list for a first kidney transplantation between 1999 and 2004.…”
mentioning
confidence: 99%
“…A number of studies have reported no difference in transplant outcomes whether the organs were obtained from appropriately selected post-cardiac arrest patients or from other brain-dead donors. [23][24][25] Non-heart-beating organ donation has also been described after failed resuscitation attempts after in-and out-of-hospital cardiac arrest, 26,27 but these have generally been cases in which sustained ROSC was never achieved. The proportion of cardiac arrest patients dying in the critical care unit and who might be suitable non-heartbeating donors has not been documented.…”
Section: Epidemiology Of Post-cardiac Arrest Syndromementioning
confidence: 99%
“…Uncontrolled NHBDs (Maastricht type I, II) may potentially yield a larger number of organs, but are more difficult and complex to procure due to a larger interval between cardiac arrest and organ retrieval. However, select centers have successfully developed protocols to preserve abdominal and thoracic organs from uncontrolled donors in situ using extra corporeal membranous oxygenation [61,62]. As it is unclear how the human heart will respond to the variable periods of warm hypoxia seen in these donors it is important to validate animal MP protocols using human hearts from extended criteria donor and controlled NHBD rejected for clinical use.…”
Section: Use Of Mp To Expand the Donor Poolmentioning
confidence: 99%